Androstane-3β,5α,6β,17β-tetrol trihydrate - Andrade, L. C. R. (International Union of Crystallography, 2011)
The title hydrated tetrol, C(19)H(32)O(4)·3H(2)O, was synthesized by stereoselective reduction of the compound 3β,5α,6β-trihydroxyandrostan-17-one. All rings are fused trans. The organic molecules are connected head-to-tail along the c axis via O—H⋯O hydrogen bonds. Layers of water molecules in the ab plane interconnect these chains. A quantum chemical ab initio Roothan Hartree–Fock calculation of the isolated molecule gives values for the molecular geometry close to experimentally determined ones, apart from the C—O bond lengths, whose calculated values are significantly smaller than the measured ones, probably a consequence of the involvement of the C—OH groups in the hydrogen-bonding network.